Pengaruh Interior terhadap Perilaku Pengunjung Museum House of Sampoerna Surabaya - Olivia Limantara (Intra, 2017)
House of Sampoerna Museum is one of history museums located in Surabaya. Through the collections displayed, this museum wants to introduce the history of Sampoerna company. One of the indicators to know whether this goal has been achieved is by knowing the behavior of the visitors during their visit inside the museum. This study analyzed how interior aspects of this museum affect visitors’ behavior to know whether the purpose of the museum has been achieved. Behavior setting theory was used which resulted in observation, questionnaires, and interview datas. These data are later analyzed using mixed methods. The results of the analysis are explained descriptively, showing that the interior aspects of the museum such as layout, circulation, orientation, and museum elements influence visitor’s behavior of House of Sampoerna Museum Surabaya.